A multicenter comparative study of cefepime versus broad-spectrum antibacterial therapy in moderate and severe bacterial infections - Badaró,Roberto (2002)
The safety and efficacy of cefepime empiric monotherapy compared with standard broad-spectrum combination therapy for hospitalized adult patients with moderate to severe community-acquired bacterial infections were evaluated. In an open-label, multicenter study, 317 patients with an Acute Physiology and Chronic Health Evaluation (APACHE II) score ranging from >5 to =19 were enrolled with documented pneumonia (n=196), urinary tract infection (n=65), intra-abdominal infection (n=38), or sepsis (n=18). Patients were randomly assigned 1:1 to receive cefepime 1 to 2 g IV twice daily or three times a day or IV ampicillin, cephalothin, or ceftriaxone ± aminoglycoside therapy for 3 to 21 days. For both treatment groups, metronidazole, vancomycin, or macrolide therapy was added as deemed necessary. The primary efficacy variable was clinical response at the end of therapy. Two hundred ninety-six (93%) patients met evaluation criteria and were included in the efficacy analysis. Diagnoses included the following: 180 pneumonias (90 cefepime, 90 comparator), 62 urinary tract infections (29 cefepime, 33 comparator), 37 intra-abdominal infections (19 cefepime, 18 comparator), and 17 sepses (8 cefepime, 9 comparator). At the end of therapy, overall clinical success rates were 131/146 (90%) for patients treated with cefepime vs 125/150 (83%) for those treated with comparator (95% confidence interval [CI]: - 2.6% to 16.3%). The clinical success rate for patients with community-acquired pneumonia, the most frequent infection, was 86% for both treatment groups. Among the patients clinically evaluated, 162 pathogens were isolated and identified before therapy. The most commonly isolated pathogens were Escherichia coli (n=49), Streptococcus pneumoniae (n=29), Haemophilus influenzae (n=14), and Staphylococcus aureus (n=11). Bacteriologic eradication/presumed eradication was 97% for cefepime vs 94% for comparator-treated patients. Drug-related adverse events were reported in 16% of cefepime patients and 19% of comparator patients. In conclusion, cefepime had higher cure rates compared with broad-spectrum combination therapy as an initial empiric treatment for hospitalized patients with moderate to severe community-acquired infections, including urinary tract infections, intra-abdominal infections, and sepsis.